Analisis Kualitas Pelayanan Terhadap Kepuasan Pasien BPJS Mandiri di Puskesmas Mpunda Kota Bima - Ahdyat Juwindra; Firman (Universitas Ahmad Dahlan, 2019)
The Social Security Administrative Body or abbreviated as BPJS is a social security program that has a legal entity. It is a form of guarantee formed by the government to ensure that all people can fulfill their basic needs. BPJS in Indonesia implements a national social security system based on the principles of humanity, benefits, and social justice for all Indonesian people. The purpose of holding BPJS is to provide guarantees that meet the basic needs of a decent life for every participant and family member. The good or bad service quality of a puskesmas will be determined and have a direct impact on the participants. If the puskesmas has good service, the participants will be satisfied, and the quality of service will be good and the puskesmas has a good image in the community, and vice versa. The good or bad quality of puskesmas services can be determined by the views of patients or service user participants who visit the puskesmas. The purpose of this study was to analyze the satisfaction of independent BPJS patients with services at the Mpunda Health Center. The type of research used is quantitative research with a descriptive study design. Researchers only observe without treating the object to be studied, as well as by describing the state of the environment under study. The sample of this study were BPJS Mandiri participants with a total sample of 179 people. Sampling was carried out by taking into account the inclusion and exclusion criteria. Based on the results of the study, it was found that BPJS Mandiri Puskesmas Mpunda patients were dissatisfied with the structural components, namely the availability of officers, service schedules, drug availability, room cleanliness, room comfort, completeness of facilities and availability of information facilities. BPJS independent patients at the Mpunda Health Center were dissatisfied with the process components, namely waiting time for registration, officer explanations, officer inspections, officer attitudes, service speed, officer responsiveness, system availability and complaints. Independent BPJS patients at the Mpunda Health Center are dissatisfied with the services provided by the Mpunda Health Center, Bima City